Virtual Influencers, Real Impact: A Narrative Review on Credibility, Generational Trust, and Purchase Intention in Digital Marketing - Ananda, Annisa Rizki; Putra, Muhammad Nuur Tanja; Azhar, Muhammad Irwan Yazid (Sinergi International Journal of Communication Sciences, 2025)
This narrative review investigates the impact of influencer marketing on consumer behavior, with a focus on the dimensions of influencer credibility, parasocial relationships, generational response differences, and the emerging role of virtual influencers. The study aims to synthesize current literature and provide an integrative framework to understand how these factors shape consumer purchase intent in digital contexts. Using a narrative synthesis methodology, the review draws from recent empirical studies and theoretical models to analyze how psychological mechanisms and systemic factors interact in influencer marketing. Key findings reveal that credibility attributes such as trustworthiness, expertise, attractiveness, authenticity, and consistency are fundamental in influencing consumer trust and brand engagement. Parasocial relationships enhance emotional connections between influencers and followers, mediating the effectiveness of endorsement. Furthermore, generational differences in digital behavior necessitate personalized communication strategies. The review also highlights the dual nature of virtual influencers, offering consistent branding but facing challenges in perceived authenticity. Systemic influences—such as platform algorithms, regulatory frameworks, and ethical standards—play a critical role in either enabling or constraining the reach and effectiveness of campaigns. This review underscores the urgency for adaptive, ethical, and transparent marketing practices. It recommends future research into culturally inclusive frameworks, long-term engagement metrics, and data-driven personalization strategies. The findings contribute to a deeper understanding of digital consumer psychology and provide actionable insights for both scholars and marketing practitioners in the age of social media.